PROGRAM BIMBINGAN KOSELING UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA - Sipayung, Regina; Berutu, Ira Seviana; Hutajulu, Yohani; Pardosi, Selma Roulina; Mawati, Maria Sri; Siburian, Enzel Ulina (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This study aims to develop an effective guidance and counseling (BK) program to improve elementary school students' social skills. Social skills, such as communication skills, cooperation, empathy, and conflict resolution, are important aspects in supporting students' academic success and psychosocial development. However, many students still face obstacles in mastering these skills. This study uses an Action Research approach with the Kemmis and McTaggart model which includes planning, action, observation, and reflection. Data were collected through observation, interviews, field notes, and open-ended questionnaires, and analyzed using a thematic qualitative approach. The program developed consists of basic services, responsive services, and system support, arranged in weekly modules for eight meetings. Implementation was carried out in two cycles in grade V of elementary school, with evaluation through observation of social skills attitudes during the implementation of the treatment. The results showed an average increase in students' social skills of 23%, with the communication and cooperation aspects experiencing the highest increase. These findings confirm the effectiveness of the BK program based on play and discussion activities in developing students' social skills. The participation of teachers and parents also plays an important role in the success of the program. This research contributes to the development of contextual and collaborative BK services at the elementary school level.